2020
DOI: 10.1101/2020.06.22.165100
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COPII Sec23 proteins form isoform-specific ER exit sites with differential effects on polarized growth

Abstract: 30COPII, a coat of proteins that form vesicles on the ER, mediates vesicle 31 traffic from the ER to the Golgi. In contrast to metazoans that have few genes 32 encoding each COPII component, plants have expanded these gene families 33 leading to the hypothesis that plant COPII has functionally diversified. Here, we 34 analyzed the gene families encoding for the Sec23/24 heterodimer in the moss 35 Physcomitrium (Physcomitrella) patens. In P. patens, Sec23 and Sec24 gene 36 families are each comprised of seven g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 74 publications
(120 reference statements)
0
7
0
Order By: Relevance
“…However, in Δsabre , both the actin and microtubule cytoskeletons were not significantly altered, suggesting that SABRE’s impact on cell expansion is independent of the cytoskeleton. Of note, a recent study demonstrated that protonemata lacking COPII function, which mediates ER to Golgi transport, exhibited aggregated ER and polarized growth defects (Chang et al, 2020), suggesting that SABRE’s influence on the ER might alter ER secretory function. In contrast to defects in COPII function, which generally reduces secretion, Δsabre defects appear to specifically affect a subset of secretory cargo, given that delivery of the plasma membrane protein SNAP-TM-mCherry was unaffected in Δsabre but affected in COPII mutants (Chang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, in Δsabre , both the actin and microtubule cytoskeletons were not significantly altered, suggesting that SABRE’s impact on cell expansion is independent of the cytoskeleton. Of note, a recent study demonstrated that protonemata lacking COPII function, which mediates ER to Golgi transport, exhibited aggregated ER and polarized growth defects (Chang et al, 2020), suggesting that SABRE’s influence on the ER might alter ER secretory function. In contrast to defects in COPII function, which generally reduces secretion, Δsabre defects appear to specifically affect a subset of secretory cargo, given that delivery of the plasma membrane protein SNAP-TM-mCherry was unaffected in Δsabre but affected in COPII mutants (Chang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, a recent study demonstrated that protonemata lacking COPII function, which mediates ER to Golgi transport, exhibited aggregated ER and polarized growth defects (Chang et al, 2020), suggesting that SABRE’s influence on the ER might alter ER secretory function. In contrast to defects in COPII function, which generally reduces secretion, Δsabre defects appear to specifically affect a subset of secretory cargo, given that delivery of the plasma membrane protein SNAP-TM-mCherry was unaffected in Δsabre but affected in COPII mutants (Chang et al, 2020). In a surprising connection, a study in Drosophila discovered hobbit, a protein that the authors report is conserved broadly across eukaryotes (Neuman and Bashirullah, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in ∆sabre , both the actin and microtubule cytoskeletons were not affected, suggesting that SABRE’s impact on cell expansion is independent of the cytoskeleton. Of note, a recent study demonstrated that protonemata with impaired COPII function, which mediates ER to Golgi transport, exhibited aggregated ER and polarized growth defects ( Chang et al, 2020 ), suggesting that SABRE’s influence on the ER might alter ER secretory function. In contrast to defects in COPII function, which generally reduces secretion, ∆sabre defects appear to specifically influence a subset of secretory cargo.…”
Section: Discussionmentioning
confidence: 99%